Meta‐analysis: Interleukin 6 gene ‐174G/C polymorphism associated with type 2 diabetes mellitus and interleukin 6 changes. Issue 12 (7th May 2021) - Cheng, Hao; Zhu, Wenbin; Zhu, Mou; Sun, Yan; Sun, Xiaojie; Jia, Di; Yang, Chao; Yu, Haitao; Zhang, Chunjing
Abstract: The gene coding interleukin 6 ( IL‐6 ) is a promising candidate in predisposition to type 2 diabetes mellitus (T2DM). This study aimed to meta‐analytically examine the association of IL‐6 gene −174G/C polymorphism with T2DM and circulating IL‐6 changes across −174G/C genotypes. Odds ratio (OR) and standard mean difference (SMD) with 95% confidence interval (CI) were calculated. Twenty‐five articles were meta‐analysed, with 20 articles for T2DM risk and 9 articles for circulating IL‐6 changes. Overall, there was no detectable significance for the association between −174G/C polymorphism and T2DM, and this association was relatively obvious under dominant model (OR: 0.82, 95% CI: 0.56‐1.21). Improved heterogeneity was seen in some subgroups, with statistical significance found in studies involving subjects of mixed races (OR: 0.63, 95% CI: 0.46‐0.86). Begg's and filled funnel plots, along with Egger's tests revealed week evidence of publication bias. In genotype‐phenotype analyses, carriers of −174CC and −174CG genotypes separately had 0.10 and 0.03 lower concentrations (pg/mL) of circulating IL‐6 than −174GG carriers. Albeit no detectable significance for the association of −174G/C with T2DM, our findings provided suggestive evidence on a dose‐dependent relation between −174G/C mutant alleles and circulating IL‐6 concentrations, indicating possible implication of this polymorphism in the pathogenesis of T2DM.